Combination Concept of LSB and PlayFair Cipher for Optimizing Data Security - Hidajat, Moch. Sjamsul; Ery Mintorini (UPT P2M State Polytechnic of Malang, 2024)
Data security is now something that is very necessary, with the aim of ensuring that important data and information does not fall into the hands of unauthorized people. The widespread data exchange process provides opportunities for unauthorized parties to take, copy or steal the exchanged data. This is what triggers the importance of securing data when exchange occurs. In the field of computer science, there are many ways that data can be secured. These methods include the concepts of steganography and cryptography. Steganography is a way to hide data in various media, while cryptography is a way to encode data into a form that has no meaning. This research aims to design a system to secure messages in the form of text data using the Playfair cipher cryptography method and Least Significant Bit (LSB) steganography using image media and the image containing the message is not visible to the eye that the image contains a secret message